Relationship between Financial Knowledge, Financial Attitude and Financial Skills and Millennial Investment Decisions - Puji Astuti; Poppy Laksita Rini; Muhammad Ali Fikri (Journal of Management and Business Environment (JMBE), 2022)
Investment as an activity to put capital into an object, institution or party for future benefits is currently important. However, lack of understanding on the basic concepts of investment by the millennial causes many inappropriate financial decisions. Without a proper basic understanding, they may not know the right time to prepare emergency fund. The purpose of this study was to determine the relationship between financial knowledge, financial attitudes and financial skills on investment decisions of the millennials. The method used in this research is a quantitative method in which analysis was based on statistical procedures using the SmartPls. The samples were the students of FEB Ahmad Dahlan University to whom the questionnaires were distributed. The number of samples was determined by considering the population that is homogeneous. The tool for analytical test was Smart PLS v.3.3.9 with the SEM (Structural Equation Modeling) as the analysis method. The results show that financial knowledge has no significant effect.